Strategi Dinas Pariwisata dan Kebudayaan dalam Mengembangkan Objek Wisata Air Terjun Sipiso-piso di Kecamatan Merek Kabupaten Karo - Feigy B Imel Br Sembiring; Sally Marisa Sihombing (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The strategies identified by the Tourism Office in developing the Sipiso-piso waterfall tourist attraction are (1) Monitoring every week to find out what needs to be improved and monitor the level of tourist visits to the Sipiso-piso waterfall and evaluate the monitoring. in order to find out what other strategies can develop the Sipiso-piso waterfall and increase tourists, (2) Involve all parties in the development of the Sipiso-piso waterfall, such as the community and business people who sell in the Sipiso-piso waterfall area, so that development is carried out can produce maximum results. (3) Conducting training for business actors such as tourism awareness socialization which is carried out once a year, (4) Coordination with all offices related to tourism in developing the Sipiso-piso waterfall tourist attraction. (5) Planning programs that can be done in developing the Sipiso-piso waterfall and attracting tourists to visit the Sipiso-piso waterfall.